Obtaining and Investigation of the β-Cyclodextrin Inclusion Complex with Vitamin D3 Oil Solution - Bakirova, R.; Nukhuly, A.; Iskineyeva, A.; Fazylov, F.; Burkeyev, M.; Mustafayeva, A.; Minayeva, Y.; Sarsenbekova, A. (Scientifica, 2020)
Background. )e research results of fat-soluble vitamin D3 (cholecalciferol) encapsulation with β-cyclodextrin have been presented in this work. )e vitamin D3 inclusion complex with β-cyclodextrin was obtained under microwave radiation. )e surface morphology of obtained clathrate inclusion complexes was described with the help of a scanning electron microscope. )e thermographic measurement results on a differential scanning calorimeter have been presented. )e activation energy of the β-cyclodextrin : vitamin D3 clathrate complex thermal oxidative destruction reaction was calculated. )e clathrate thermal destruction kinetic parameters were determined. )e inclusion complex spectral properties were characterized by IR-Fourier and 1Hand 13C NMRspectroscopy.)eexistence of β-cyclodextrin inclusion complex with vitamin D3 in a 2 :1 ratio was confirmed by the experimental results. )e activation energy of thermal destruction of the inclusion complex of β-cyclodextrin with vitamin D3 was calculated using four different methods.